Das differentialgeometrische Zusammenhangsobjekt der p-fach zusammengesetzten Mannigfaltigkeit - Bliznikas, V. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Близникас. Объект дифференциально-геометрической связности p-кратного составного многообразия V. Bliznikas. p-kartotinės sudėtinės daugdaros diferencialinio geometrinio sąryšio objektas